PGC-1/Spargel Counteracts High-Fat-Diet-Induced Obesity and Cardiac Lipotoxicity Downstream of TOR and Brummer ATGL Lipase - Soda Diop; Jumana Bisharat‐Kernizan; Ryan T. Birse; Sean Oldham; Karen Ocorr; Rolf Bodmer (2015)
Obesity and metabolic syndrome are associated with an increased risk for lipotoxic cardiomyopathy, which is strongly correlated with excessive accumulation of lipids in the heart. Obesity- and type-2-diabetes-related disorders have been linked to altered expression of the transcriptional cofactor PGC-1α, which regulates the expression of genes involved in energy metabolism. Using Drosophila, we identify PGC-1/spargel (PGC-1/srl) as a key antagonist of high-fat diet (HFD)-induced lipotoxic cardiomyopathy. We find that HFD-induced lipid accumulation and cardiac dysfunction are mimicked by reduced PGC-1/srl function and reversed by PGC-1/srl overexpression. Moreover, HFD feeding lowers PGC-1/srl expression by elevating TOR signaling and inhibiting expression of the Drosophila adipocyte triglyceride lipase (ATGL) (Brummer), both of which function as upstream modulators of PGC-1/srl. The lipogenic transcription factor SREBP also contributes to HFD-induced cardiac lipotoxicity, likely in parallel with PGC-1/srl. These results suggest a regulatory network of key metabolic genes that modulates lipotoxic heart dysfunction.